Effects of different doses of metformin treatment for 6 months on aberrant crypt foci in Chinese patients with impaired glucose tolerance. Issue 1 (January 2015) - Zhao, Xiaotong; Li, Yongxiangi; Chen, Mingwei; Chen, Yan; Dai, Yao; Wang, Youming; Xie, Huijuan
<x xml:space="preserve">Abstract</x> This research was carried out to evaluate the chemopreventive effects of different doses of metformin treatment for 6 months on rectal aberrant crypt foci (ACF) in patients with impaired glucose tolerance (IGT). A total of 120 Chinese patients with IGT were enrolled and assigned randomly to a low-dose metformin group (n=30, metformin at 250 mg/day), a middle-dose metformin group (n=30, metformin at 500 mg/day), a high-dose metformin group (n=30, metformin at 1500 mg/day), and a control (untreated with metformin) group (n=30). Each participant was followed for 6 months by protocol, and the number of ACF per patient in the above four groups was examined by magnifying colonoscopy before, and after 3 and 6 months of, treatment. The mean ACF numbers in both the middle-dose and the high-dose metformin groups were significantly decreased at 3 as well as 6 months of treatment, whereas they did not change in the low-dose metformin and the untreated groups. In the high-dose metformin group, BMI, waist circumference, fasting plasma glucose, homeostatic model assessment of insulin resistance index, and 2-h plasma glucose were significantly decreased. However, no such change was observed in the middle-dose metformin group. Changes in the ACF number correlated positively with changes in the homeostatic model assessment of insulin resistance (r=0.273, P=0.013), BMI (r=0.241, P=0.042), and 2-h plasma glucose (r=0.252, P=0.037), respectively, in the high-dose metformin group, but no such correlation was observed in the middle-dose metformin group. Metformin suppressed ACF formation in IGT patients in a dose-dependent manner, possibly through direct and indirect (attenuating insulin resistance) mechanisms.